Time Trends and Excess Mortality Compared to Population Controls after a First-Time Pulmonary Embolism or Deep Vein Thrombosis - Glise Sandblad, Katarina; Svensson, Carl Johan; Svennerholm, Kristina; Philipson, Jacob; Pivodic, Aldina; Schulman, Sam; Tavoly, Mazdak (Thrombosis and Haemostasis, 2024)
Recent data on temporal trends in excess mortality for patients with pulmonary embolism (PE) and deep vein thrombosis (DVT) compared with the general population are scarce.A nationwide Swedish register study conducted from 2006 to 2018 including 68,960 PE and 70,949 DVT cases matched with population controls. Poisson regression determined relative risk (RR) for 30-day and 1-year mortality trends while Cox regression determined adjusted hazard ratios (aHRs). A significance level of 0.001 was applied.In PE cases, both 30-day mortality (12.5% in 2006 to 7.8% in 2018, RR: 0.95 [95% CI: 0.95–0.96], p < 0.0001) and 1-year mortality (26.5 to 22.1%, RR: 0.98 [0.97–0.98], p < 0.0001) decreased during the study period. Compared with controls, no significant change was seen in 30-day (aHR: 33.08 [95% CI: 25.12–43.55] to 24.64 [95% CI: 18.81–32.27], p = 0.0015 for interaction with calendar year) or 1-year (aHR: 5.85 [95% CI: 5.31–6.45] to 7.07 [95% CI: 6.43–7.78], p = 0.038) excess mortality. The 30-day excess mortality decreased significantly (aHR: 39.93 [95% CI: 28.47–56.00) to 24.63 [95% CI: 17.94–33.83], p = 0.0009) in patients with PE without known cancer before baseline, while the excess 1-year mortality increased (aHR: 3.55 [95% CI: 3.16–3.99] to 5.38 [95% CI: 4.85–5.98], p < 0.0001) in PE cases surviving to fill a prescription of anticoagulation. In DVT cases, 30-day and 1-year mortality declined, while excess mortality compared with controls remained stable.In general, the improved mortality following PE and DVT paralleled population trends. However, PE cases without cancer had decreasing excess 30-day mortality, whereas those surviving to fill a prescription for anticoagulant medication showed increasing excess 1-year mortality.
Keywords: deep vein thrombosis; pulmonary embolism; mortality; trends